2016
DOI: 10.1192/bjp.bp.114.149997
|View full text |Cite
|
Sign up to set email alerts
|

Patient outcomes following discharge from secure psychiatric hospitals: Systematic review and meta-analysis

Abstract: BackgroundSecure hospitals are a high-cost, low-volume service consuming around a fifth of the overall mental health budget in England and Wales.AimsA systematic review and meta-analysis of adverse outcomes after discharge along with a comparison with rates in other clinical and forensic groups in order to inform public health and policy.MethodWe searched for primary studies that followed patients discharged from a secure hospital, and reported mortality, readmissions or reconvictions. We determined crude rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
94
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(109 citation statements)
references
References 67 publications
(211 reference statements)
8
94
2
2
Order By: Relevance
“…154 Recent research has found a great deal of variation in outcomes internationally, with mortality rates varying between 289 and 2828 per 100,000 patient-years, readmission rates varying between 2926 and 16,641 per 100,000 patient-years and reconviction rates varying between 0 and 24,244 per 100,000 patient-years. 25 It is not clear how England compares in these outcomes internationally, although there is some indication that outcomes may be worse there than in other countries. 150 This may be due to ineffective treatment, although a more likely explanation might be the restrictive nature of services, reducing opportunities for patients to engage in varied prosocial activities, and policies (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…154 Recent research has found a great deal of variation in outcomes internationally, with mortality rates varying between 289 and 2828 per 100,000 patient-years, readmission rates varying between 2926 and 16,641 per 100,000 patient-years and reconviction rates varying between 0 and 24,244 per 100,000 patient-years. 25 It is not clear how England compares in these outcomes internationally, although there is some indication that outcomes may be worse there than in other countries. 150 This may be due to ineffective treatment, although a more likely explanation might be the restrictive nature of services, reducing opportunities for patients to engage in varied prosocial activities, and policies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Given this complexity, it is not surprising that rigorous evidence of 'what works' in secure care is limited. 25 Interventions typically tackle a range of treatment needs, and may include pharmacological, individual and group psychological interventions to improve symptoms as well as to reduce risk (e.g. of violent and sexual offending).…”
Section: Treatment In Secure Care and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions aiming to improve the transition from hospital to home have been tested in studies and partly summarized in systematic reviews. These systematic reviews have either focused on a wide range of interventions, including preintervention and postintervention components (7,21), specific patient groups (22), and settings or services (23,24). For example, Vigod et al (7) found evidence from nonrandomized trials indicating that psychoeducational interventions help to improve disease management and everyday skills, which may reduce readmission rates of psychiatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…Despite several reports outlining outcomes for offender patients discharged from forensic psychiatry hospitals in European countries (Buchanan, 1998;Coid, Hickey, Kahtan, Zhang, & Yang, 2007;Davies, Clarke, Hollin, & Duggan, 2007;Fazel, Fiminska, Cocks, & Coid, 2016;Tabita, De Santi, & Kjellin, 2012), information is limited for those within Japan (Ando, Soshi, Nakazawa, Noda, & Okada, 2016). Hence, we conducted a cohort study of offenders with mental disorder discharged from designated MTSA facilities in Japan.…”
Section: Introductionmentioning
confidence: 99%